A nomogram for prediction of deep venous thrombosis risk in elderly femoral intertrochanteric fracture patients: A dual-center retrospective study - Xiang, Guangheng; Dong, Xiaoyu; Lin, Shenglei; Cai, Leyi; Zhou, Feiya; Luo, Peng; Zhu, Juanjuan (Frontiers in Surgery, 2023)
Abstract Objective: Deep venous thrombosis (DVT) of the lower extremity is a common perioperative complication of femoral intertrochanteric fracture. This study aimed to identify the risk factors of lower extremity deep vein thrombosis (DVT) in elderly femoral intertrochanteric fracture patients and establish a nomogram model. Methods: From August 2014 to June 2021, a total of 1652 femoral intertrochanteric fracture patients over the age of 65 were enrolled in our study. We distinguished independent risk factors by univariate and multivariate Cox analyses. A nomogram model was then built, and the discriminative and calibration of the model was evaluated through receiver operating characteristics (ROC) and calibration plots. Results: A total of 378 patients developed DVT (292 in the training group, 86 in the validation group) while the remaining patients did not. According to the univariate and multivariate Cox analyses results, age (OR = 1.07, 95%CI: 1.04 – 1.10), fibrinogen (OR = 2.09, 95%CI: 1.68 – 2.60), D-dimer (OR = 1.33, 95%CI: 1.27 – 1.40), time from injury to admission (OR = 1.78, 95%CI: 1.55 – 2.05), functional status (OR = 4.21, 95%CI: 2.86 – 6.20), and diabetes (OR = 1.65, 95%CI: 1.10 – 2.48) were identified as independent risk factors of DVT. The ROC values for DVT of the training and validation group were 0.862 and 0.912, and the P-value of the Hosmer-Lemeshow calibration test was 0.767. Conclusion: This nomogram model can be used to predict the probability of preoperative DVT in elderly patients with femoral intertrochanteric fracture and guide physician in perioperative thrombosis management.